2012
DOI: 10.1155/2012/194397
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Studies of Neural Network Control for One-Wheel Mobile Robot

Abstract: This paper presents development and control of a disc-typed one-wheel mobile robot, called GYROBO. Several models of the onewheel mobile robot are designed, developed, and controlled. The current version of GYROBO is successfully balanced and controlled to follow the straight line. GYROBO has three actuators to balance and move. Two actuators are used for balancing control by virtue of gyro effect and one actuator for driving movements. Since the space is limited and weight balance is an important factor for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The work [12] presents the development and control of a disc-typed one-wheel mobile robot, called GYROBO. Two actuators are used for balancing control by virtue of gyro effect and one actuator for driving movements.…”
Section: Impact Of Vigilancementioning
confidence: 99%
“…The work [12] presents the development and control of a disc-typed one-wheel mobile robot, called GYROBO. Two actuators are used for balancing control by virtue of gyro effect and one actuator for driving movements.…”
Section: Impact Of Vigilancementioning
confidence: 99%
“…Undeniably, they will be utilized in industry as an alternative to the skilled workforce doing high-risk activities in the near future. To control robots for a variety of challenging tasks, researchers have used efficient robust controllers, such as practical velocity tracking control [ 4 ], dynamic state feedback control [ 5 ], fuzzy PD control [ 6 ], and neural network control [ 7 ]. Specifically, Solís-Perales and Peón-Escalante [ 8 ] used robust adaptive tracking control for a class of robot manipulators having model uncertainties.…”
Section: Introductionmentioning
confidence: 99%
“…Fruitful research outcomes about a single-wheel mobile robot, Gyrover have been summarized as a book [6]. Other research activities on a single-wheel mobile robot can also be found in the literature, but they are not many [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…A history of implementing Gyrobo has been presented in the paper [9]. A neural network control technique is applied to control the balancing angle as well as trajectory tracking tasks [10]. One of difficulties of implementing a single-wheel robot is the mechanical design to have a symmetrical structure in the body and to generate enough gyro-effect to raise the whole system up.…”
Section: Introductionmentioning
confidence: 99%